Edukasi Guru PAUD tentang Status Gizi Anak di TKIT An-Nahl Kota Jambi - Dini Wulan Dari; Satiti Kawuri Putri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Human development as a whole starts from the fetus in the mother's womb and enters the golden age, namely intelligence has a very significant increase. Therefore, it is very important to pay attention to the growth, development, and nutritional intake consumed by children. The factors that cause school children to be malnourished are the consumption and knowledge of children's nutrition. In addition, the low nutritional status of school children must be corrected immediately because it has an impact on their learning abilities. Based on the results of the service team's interview to the Principal of TKIT An-Nahl Jambi City, currently TKIT An-Nahl already has a posyandu within the school environment to monitor the nutritional status of children early. However, the human resources at the TKIT do not yet have a good understanding of the nutritional status of children. The targets for this activity are providing material on children's nutritional status, training in calculating the nutritional status of PAUD children based on anthropometric measurements (BB and TB) and preparing menus and forming a driving group for improving children's nutritional status. Implementation methods include planning, implementing activities as well as monitoring and evaluation. The results of this activity were 8 people (80%), before conducting PAUD Teacher Education on Children's Nutritional Status to teachers, many did not know about children's nutritional status. after being given education about the nutritional status of children and given post-test to the audience, there was an increase from 50% to 80%. In conclusion, there was a change in good knowledge on the target and the formation of 2 teams to drive children's nutritional status